CD4+ Memory T Cells at Home in the Tissue: Mechanisms for Health and Disease - Schreiner, David; King, Carolyn G. (Frontiers in Immunology, 2018)
During the last ten years, a population of clonally expanded T cells that take up permanent residence in non lymphoid tissues has been identified. The localization of these tissue resident memory (TRM) cells allows them to rapidly respond at the site of antigen exposure, making them an attractive therapeutic target for various immune interventions. Although most studies have focused on understanding the biology underlying CD8 TRMs, CD4 T cells actually far outnumber CD8 T cells in barrier tissues such as lung and skin. Depending on the immune context, CD4 TRM can contribute to immune protection, pathology or tissue remodeling. Although the ability of CD4 T cells to differentiate into heterogeneous effector and memory subsets has been well established, how this heterogeneity manifests within the TRM compartment and within different tissues is just beginning to be elucidated. In this review we will discuss our current understanding of how CD4 TRMs are generated and maintained as well as a potential role for CD4 TRM plasticity in mediating the balance between beneficial and pathogenic immune responses.